ANALYSIS OF THE IMPACT MITIGATION OF THE BITUNG – SERPONG TOLL ROAD CONSTRUCTION ON ENVIRONMENTAL CONDITIONS - Novyangga, Purnama; Tumilar, Randyr Eka; Saputra, Rangga; Saputra, M. Farid Ardiansyah Aris (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Roads are a form of primary infrastructure that plays a vital role in life. Banten Province is connected by several national roads and toll roads. These national roads and toll roads also connect regencies and cities in the area. With the increasing density of road users, of course congestion cannot be avoided, because national roads and toll roads will be passed by vehicles both going to and leaving the Banten Province area. The current traffic flow conditions through toll roads are quite dense (saturated), so that to overcome congestion, it is necessary to build alternative roads with a higher level of quality and adequate levels of accessibility and mobility. The construction of toll road infrastructure, such as the Bitung-Serpong Toll Road, has a significant impact on the environment. This journal aims to analyze the environmental impacts caused by this toll road construction project, including changes in land use, impacts on ecosystems, pollution, and socio-economic impacts. Through this study, it is hoped that recommendations can be provided for mitigating possible negative impacts.